Sustainable innovation pathway for mechanical products by inducing characteristic parameters. (August 2021) - Nie, Zifeng; Zhang, Peng; Wang, Fang; Wang, Zizhen
Abstract: Mechanical product design per experiences of designers consumes unproportionally high manpower and time, as well as requires high relevance of designers' experiences. To address this issue and extend the specific design innovation for general application, innovation methods of mechanical products have become a hot research topic. However, the currently available innovation methods are limited to specific needs of the market, exhibiting the form of discrete solutions. Thus, the innovation process is not sustainable. To this gap, this study integrates the emerging digital twin technology with engineering innovation theory and knowledge reuse concepts to establish a systematic sustainable innovation pathway (SIP) by inducing characteristic parameters. The pathway spares the demands for designer's relevant experiences and avail sustainability of existing innovation methods. The derivation of the current SIP can be divided into six steps. To start with, the existing mechanical products based on users and market requirements are analyzed to synthesize general functional requirements. The characteristic parameters corresponding to the functional requirements are derived in the second step. Characteristic parameters are then specified and the potential problems which may occur in the induction of characteristic parameters are preliminarily solved. Digital twin technology is engaged to dynamically induce characteristic parameters. During the induction process, variation of related parameters due to changes in characteristic parameters are monitored. The problems that arise in variation may suggest new schemes, which solutions indicate new innovation directions. Finally, the candidate schemes of mechanical products according to different needs are identified. The formulated innovation plan and direction are archived in a knowledge base to establish a retrievable solution that matches the SIP. The applicability of current SIP is demonstrated by innovative design exemplification of a parking space management system.